e-Book Student Worksheet Based on Socio-Scientific Issues of Batik Waste in Jetis Sidoarjo: e-Book LKPD Berbasis Socio-Scientific Issue Limbah Batik Jetis Sidoarjo - Citra Azizah; Ria Wulandari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital student worksheets are increasingly developed to support contextual science learning in junior secondary education. Specific Background: The integration of socio-scientific issues into electronic worksheets enables students to connect scientific concepts with real environmental problems, including batik wastewater in Jetis Sidoarjo. Knowledge Gap: However, contextual digital worksheets that explicitly integrate local environmental pollution issues into the topic of living organisms and their environment remain limited. Aims: This study aimed to develop an SSI-based e-book LKPD addressing Jetis batik waste as a contextual learning resource. Results: The development process involved needs analysis, content and layout design, project and investigation-based learning activities, expert validation, and instrument validity testing. The e-book contains observation, discussion, and a simple water filtration project to support understanding of ecosystem pollution. The product is accessible through a web link and FlipHTML5 platform. Novelty: The novelty lies in integrating a local batik wastewater issue into a structured digital worksheet based on socio-scientific issues. Implications: This product provides a contextual digital learning resource that supports environmental literacy and connects scientific knowledge with community-based environmental challenges. Keywords: SSI-Based E-book, Student Worksheet Development, Batik Wastewater, Environmental Literacy, Contextual Science Learning Key Findings Highlights: Digital worksheet integrates local wastewater case into ecosystem learning activities. Development includes expert validation and instrument feasibility testing. Learning tasks involve observation, discussion, and simple filtration project.